A Framing Analysis of Tempo.com, Detik.com, and Kompas.com Regarding the Appointment of Thomas Djiwandono as Deputy Governor of Bank Indonesia (A Framing Study by Pan & Kosischi) - Clarisa Rui Iswanto; Fabianus Fensi (International Journal Labs, 2026)
The appointment of Thomas Djiwandono as Deputy Governor of Bank Indonesia attracted significant media attention due to his familial connection with President Prabowo Subianto and the implications for institutional independence. This study aims to analyze how major Indonesian online media Tempo.com, Detik.com, and Kompas.com framed the appointment and constructed social reality through news reporting. A qualitative descriptive approach was employed, using framing analysis based on Pan and Kosicki's model. Six news articles published in January 2026 were selected according to predetermined criteria, and data were analyzed using the Miles and Huberman model through data reduction, presentation, and conclusion drawing. Results indicate distinct framing strategies across media outlets. During the candidacy phase, Tempo.com emphasized political relations, Detik.com focused on administrative procedures, and Kompas.com highlighted legitimacy and support. In the ratification phase, all media shifted focus toward independence, professionalism, and institutional legitimacy, reflecting editorial differences and framing dynamics. The findings demonstrate that online media not only report facts but actively shape public perception through the selection of headlines, sources, diction, and visuals. This study concludes that media framing plays a crucial role in constructing social reality, emphasizing the need for critical public media consumption. Future research should expand media scope and employ quantitative approaches to evaluate the effects of framing on public opinion.